Development of a compact torus injector system for central fuelling technology of EAST. (1st May 2022) - Zhao, Z.H.; Lan, T.; Kong, D.F.; Ye, Y.; Zhang, S.B.; Zhuang, G.; Zhang, X.H.; Hu, G.H.; Chen, C.; Wu, J.; Zhang, S.; Qi, M.B.; et al.
Abstract: In this paper, a compact torus (CT) injector system is designed for experimental advanced superconducting tokamak (EAST). The injector system consists of a coaxial electrode and four pulsed power systems and generates self-organized CT with high density and velocity. In addition, the performance of EAST-CTI is evaluated using a series of diagnostics systems. The experimental results show that the velocity, electron density, and number of particles of the CT are 56.0 km/s, 8.73 × 10 20 m -3, and 2.4 × 10 18, respectively. The detailed description and experimental results are presented in this paper.